CD4 + T cells impair tumor growth through IL-3 and TNF-dependent vascular damage - Qiaoshi Lian; Jia Nie; Jatinder Singh; Qiang Chen; Jennifer Matta; Waipan Chan; Mariah Balmaceno-Criss; Melanie S. Vacchio; Weiming Yu; Alexander D. Clark; Elijah Edmondson; Michael C. Kelly; et al. (Science, 2026)
Most cancer immunotherapy strategies are focused on direct tumor killing by immune cells, especially T lymphocytes. Clinical and conceptual limitations of these approaches create a need for additional strategies. We identified a tumor stroma–targeting mechanism in which tumor antigen–specific CD4 + T cells inhibit tumor growth through myeloid cell and tumor necrosis factor (TNF)–dependent vascular damage. Multiplex immunofluorescence and single-cell and tissue transcriptomics showed that CD4 + T cells trigger the formation of perivascular myeloid cell clusters containing “classically activated” macrophages that produce TNF in response to T cell–derived interleukin-3. TNF causes intratumoral endothelial damage and blood supply disruption, which are associated with localized tumor cell death. Thus, intratumoral antigen-triggered T cell activation can mediate antitumor effects without direct recognition of living tumor cells, thereby avoiding many of the inhibitory mechanisms that limit anti-tumor immunity.